Metabolic changes in the eye lens in the progression of cataract - A. D. Chuprov; S. V. Notova; O. V. Marshinskaia; T. V. Kazakova (Acta Biomedica Scientifica, 2024)
Background. Cataract is one of the main causes of decreased visual acuity in the world, and therefore scientists are continuing researches on the mechanisms of development of this ophthalmic pathology.The aim. To study metabolic changes in a cloudy lens using an experimental model.Materials and methods. The study was carried out on adult male Wistar rats (n = 60), which were divided into control (n = 30) and experimental (n = 30) groups. Experimental cataract were simulated by daily ultraviolet irradiation (λ = 300–350 nm) during 6 months for 20 minutes. At the months 2, 4 and 6 of the study, we carried out a biomicroscopic examination of the anterior eye of animals using a slit lamp to monitor the development of cataract. Lenses were collected to determine the content of stearoyl-coenzyme-A desaturases and melatonin using enzyme immunoassay.Results. At the stage of initial cataract, the content of the stearoyl-coenzyme A desaturase was statistically significantly lower than the control values by 38 %; at the stage of immature cataract – by 30 %; at the stage of mature cataract – by 15.4 %. It was revealed that at the month 6 of the study, the concentration of melatonin in lens homogenates was 17 % lower when compared with the control. A statistically significant correlation was established between stearoyl-coenzyme A desaturase and melatonin (r = 0.32).Conclusion. Melatonin and stearoyl-coenzyme A desaturase play an important role in a number of biochemical processes that ensure the proper functioning of the visual analyzer. Changes in the concentration of these biological molecules can play a key role in the pathogenesis of cataract and a number of other ophthalmic diseases